التضخم النقدي وأثره في رد القروض (رؤية شرعية) الحالة العراقية أنموذجا - يحيى، بكر رعد توفيق (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2011)
This study aims to shed light on the issue of money and some of the injunctions related to it, such as its definition, functions, a brief historical background, the injunctions that distinguish paper currency from metal currency and the changes that impact paper currency, as the problem of monetary inflation is linked with paper currency. The study also discusses the concept of monetary inflation, its causes, types, methods of measurement and its impact on the repayment of loans. In this regard, the study presents and discusses the opinions and evidences of contemporary jurists concerning this issue, and identifies the juristic maxims that govern it. Moreover, the study states that an increase in the amount of loan in order to deal with the issue of inflation is not considered usury, when both contracting parties agree to take into consideration the issue of monetary inflation when concluding a loan agreement. The study devotes an entire chapter to the Iraqi case and presents it as an example of a Muslim country that suffers from such a phenomenon. In this context, the study outlines the development of the inflation phenomenon in the Iraqi economy and its causes. Furthermore, the study discusses the impact of the Iraqi Dinar collapse on the repayment of loans, in addition to relying on the statistics issued by the Ministry of Planning and the Iraqi Central Bank in presenting the price index and the rates of inflation. The study affirms that the preponderant view concerning this issue is for both parties to shoulder the harm resulting from monetary inflation, which is the opinion applied by the people of Iraq in solving this issue. The study relies on several methodologies, which are inductive, descriptive, analytical and comparative methodologies.